The Baiga - Elwin, Verrier; Hutton, J. H. (New Delhi Gyan publishing house, 2007)
The Baiga tribe is one of the important tribes in Central India. It has a long tradition and least affected by the modern civilisation. It is a treasure of knowledge, a must for all scholars and anthropologists. About The Author:- Verrier Elwin (1902-64), was unquestionably the pioneering scholar of India$1 (Bs tribal peoples, an advisor on tribal affairs to the Government of India. Contents:- General Introduction The Baiga Livelihood Bewar Cultivation The Life- Stories.s